Towards expenditure rules and fiscal sanity in the euro area - Sebastian Hauptmeier; Jesus Sanchez Fuentes; Ludger Schuknecht (European Central Bank (ECB), 2010)
The study looks at primary expenditure developments in the euro area, its three largest members and four “macro-imbalances” countries for the period 1999-2009. It compares actual expenditure trends with those that would have prevailed if countries had followed neutral policies based on expenditure rules since the start of EMU. It also calculates the implications for debt trends. It finds that, all sample countries except Germany applied expansionary expenditure policies. This resulted in much higher expenditure and debt paths compared to a counterfactual neutral expenditure stance. Simple and prudent rules-based spending policies could have led to much safer fiscal positions much more in line with the EU's Stability and Growth Pact rules.
Keywords: E17; E61; E65; H50; H60; 330; Expenditure policies; expenditure rules; fiscal stance; public debt; sustainability; Europäischer Stabilitätsmechanismus; Öffentliche Ausgaben; Öffentliche Schulden; Finanzpolitik; Nachhaltigkeit; Eurozone; Deutschland; Frankreich; Italien; Griechenland; Irland; Portugal; Spanien